Chronic Postoperative Pain: Comprehending It to Intervene - Oliveira, Lorraine Ariel Duarte; Rocha, Carolina Alves Araújo; Silva, Ledismar José (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
It is estimated that between 266.2 and 359.5 million operations were performed in 2012 worldwide, and this number is on the rise. Chronic postoperative pain (CPOP) is the most important and still neglected postoperative complication, with a multifactorial causality, leading to a major impact on morbidity rates, high costs for the public health system, and direct and negative effects on the quality of life of the patients. The present systematic literature review aimed to elucidate the processes of postoperative pain chronification, biopsychosocial factors, risk factors, management of pain, and types of surgical procedures mainly associated with it. The review was based on the methodological recommendations of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The following databases were consulted: the Medical Literature, Analysis, and Retrieval System Online (MEDLINE), the Latin American and Caribbean Health Sciences Literature (LILACS), the Scientific Electronic Library Online (SciELO), and the Cochrane Central Register of Controlled Trials (CENTRAL). After reading the selected articles, the following surgical specialties were chosen to be addressed: general, orthopedics, breast cancer, gynecology, obstetrics, and thoracic. In conclusion, a deficient management of acute postoperative pain is the main risk factor for the development of CPOP. To prevent CPOP, training programs for healthcare professionals should be implemented to improve their skills and knowledge of the management of pain before, during, and after surgeries. It is also necessary to conduct more in-depth studies on the evaluation and management of this condition.
Keywords: postoperative pain; chronic pain; pain management